KARAKTER KOLABORATIF DAN MANDIRI PESERTA DIDIK SEKOLAH DASAR DALAM PEMBELAJARAN - Anita Dongoran; Ahmad Hariandi; Ditia Erika Febriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the collaborative and independent character of elementary school students in the learning process at SDN 112/I Perumnas. The research employed a qualitative descriptive approach with a case study design to obtain an in-depth understanding of character development within an authentic learning context. Data were collected through classroom observations, semi-structured interviews with classroom teachers, and documentation analysis. The collected data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that students’ collaborative character developed through learning activities involving group discussions, cooperation in completing tasks, communication among students, and mutual respect for differing opinions. Meanwhile, students’ independent character was reflected in their ability to complete tasks responsibly, demonstrate learning initiative, and manage their own learning processes without excessive dependence on the teacher. These findings show that the learning process provides meaningful opportunities for the development of collaborative and independent character among students. Therefore, integrating character development into learning activities plays an important role in strengthening character education in elementary schools in accordance with the direction of the Merdeka Curriculum.